1999
DOI: 10.1046/j.1365-2265.1999.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular symptoms and dysfunction in subclinical hypothyroid patients: beneficial effect of L‐T4 replacement therapy

Abstract: Neuromuscular symptoms and dysfunction are rather common in subclinical hypothyroidism, and may be associated with abnormalities in serum calcium balance and surface electromyography. The ability of L-T4 treatment to reverse all these changes suggests that subclinical hypothyroidism patients may require early therapy not only to prevent progression to frank hypothyroidism, but also to improve their neuromuscular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 21 publications
2
33
0
4
Order By: Relevance
“…Some authors have described grea ter frequency of neuromuscular symptoms or muscle dysfunction on electromyography in sHT patients (7,9,11,15). Proximal muscle strength seems to be impaired in sHT, and our group previously published a cross-sectional study in which there was greater prevalence of neuromuscular complaints and altered muscle strength in sHT compared with a control group (11).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Some authors have described grea ter frequency of neuromuscular symptoms or muscle dysfunction on electromyography in sHT patients (7,9,11,15). Proximal muscle strength seems to be impaired in sHT, and our group previously published a cross-sectional study in which there was greater prevalence of neuromuscular complaints and altered muscle strength in sHT compared with a control group (11).…”
Section: Introductionmentioning
confidence: 78%
“…Although some transversal studies showed greater prevalence of neuromuscular abnormalities in sHT (7,9,11,15), little has been published about the effect of L-T4 substitution on them. To our knowledge, there is no double-blind placebo-controlled trial that evaluated muscle function until the present moment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, certain neurobehavioral and neuromuscular dysfunctions are also associated with hypothyroidism, e.g. depression, memory loss, cognitive impairment and peripheral nerve dysfunction [28][29][30]. The prevalence of depression in dialysis patients is high [31], and hypothyroidism can contribute to its development.…”
Section: Discussionmentioning
confidence: 99%
“…neurological and psychiatric or psychological, and coagulopathies. 10,[12][13][14][15] Atherosclerosis is a chronic process involving both cellular and humoral responses. In atherogenesis, leucocytes are involved in the early phase of atherosclerosis and maintain their activity during plaque formation, during which time sICAM-1 and sVCAM-1 first co-ordinate leucocyte adhesion, then their transendothelial migration.…”
Section: Discussionmentioning
confidence: 99%